2018
DOI: 10.1088/1361-6528/aaa80d
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a half-metallic state on bilayer WSe2 using doping transition metals (Cr, Mn, Fe, Co, Ni) in its interlayer

Abstract: The structural, electronic and magnetic properties of Cr, Mn, Fe, Co and Ni-doped bilayer WSe are predicted by using first principles calculations. The doped transition-metal (TM) atoms show a covalent-binding with the nearest Se atoms. The calculated electronic structures reveal that the TM Cr, Mn, Fe and Co-doped bilayer WSe exhibits a half-metallic character with a 100% spin polarization at the Fermi level, and the reason is ascribed to the strong hybridization peak between the transition metals and the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…50,51 The total density of states (TDOS) profile in Fig. S16a† shows that the TDOS curves of Mo–WSe 2 and WSe 2 almost overlap, and the bandgap (1.67 eV) is essentially the same as that of WSe 2 , 4,52–54 and this indicates that the incorporation of Mo elements alone does not significantly change the electronic structure of WSe 2 , which is consistent with the results of hydrogen adsorption free energy calculations. However, new electronic states appear near the Fermi level of Ni–WSe 2 and NiMo–WSe 2 upon Ni incorporation, which can be attributed to the splitting of energy levels caused by the introduction of doped Ni atoms, resulting in an enhancement of the H adsorption capacity of the in-plane Se atoms of WSe 2 , thereby enhancing the HER activity.…”
Section: Resultssupporting
confidence: 80%
“…50,51 The total density of states (TDOS) profile in Fig. S16a† shows that the TDOS curves of Mo–WSe 2 and WSe 2 almost overlap, and the bandgap (1.67 eV) is essentially the same as that of WSe 2 , 4,52–54 and this indicates that the incorporation of Mo elements alone does not significantly change the electronic structure of WSe 2 , which is consistent with the results of hydrogen adsorption free energy calculations. However, new electronic states appear near the Fermi level of Ni–WSe 2 and NiMo–WSe 2 upon Ni incorporation, which can be attributed to the splitting of energy levels caused by the introduction of doped Ni atoms, resulting in an enhancement of the H adsorption capacity of the in-plane Se atoms of WSe 2 , thereby enhancing the HER activity.…”
Section: Resultssupporting
confidence: 80%
“…These results show that both CuO and Co(OH) 2 exhibit typical semiconductor characteristics without the up and down spin states that exhibit a prominent splitting. [59] Figure 2e shows the energy band structure of the CPCC@ CuO@Co(OH) 2 heterojunction. There was a clear split in the spin up and down rotation state of the CuO-Co(OH) 2 heterojunction.…”
Section: Function and Mechanism Of Cpcc@cuo@co(oh) 2 Porous Heterojun...mentioning
confidence: 99%
“…Recently, it has been reported that some specially designed single-atom doping materials (SDMs) could also be used as technical solutions to solve the above problems. Due to the unique electronic properties of materials, various carbon-based materials, such as graphene, porous carbon, and carbon nitride, have been used as host materials for single-atom doping. In addition, it is a feasible method to improve the catalytic activity of multistep reaction catalysts by using the synergistic effect between metals.…”
Section: Introductionmentioning
confidence: 99%